Problematic Internet Use digunakan Ketika Kesepian pada Remaja - Yashinta, Yashinta; Hurriyati, Dwi (Jurnal Ilmiah Psyche, 2020)
This study aims to determine the relationship of loneliness with problematic internet use on boarding students on Silaberanti street in Siantan jaya Opposite Ulu 1 Palembang city. Research subjects numbered 220 people using random sampling methods. Data was collected using a 60 item problematic internet use scale and a 60 item loneliness. Realibility is generated on scale of problematic internet use of 0,955 and loneliness of 0,946.Hypothesis testing uses product moment correlation analysis techniques. Hypothesis test results showed a positive relationshif between loneliness with problematic internet use on boarding students on Silaberanti street in Siantan jaya Opposite Ulu 1 Palembang city r= 0,684 with a significance level of 0,000 (p<0,01). Loneliness in this study made an effective contribution of 46,8% to problematic internet use which can be seen from the coefficient of determination (rÂ²) that is equel to 0,468.